The Influence of Financial Performance on Public Perception Toward Organizational Transparency, Accountability, and Institutional Trust - Agus Munandar (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines the relationship between financial performance and public perception of a company. Financial performance reflects a company’s ability to manage resources, generate value, and sustain business growth. Strong financial performance indicates effective management and operational stability, which influence how stakeholders—such as investors, customers, and the public—evaluate the company’s credibility and future prospects. Design/methodology/approach – This research uses a descriptive analytical approach to analyze the relationship between financial performance and public perception. Financial performance is measured using liquidity and profitability indicators. Liquidity reflects the company’s ability to meet short-term obligations, while profitability shows its ability to generate profit. Public perception is measured through firm value, which represents how the market and stakeholders assess the company’s performance and credibility. Findings/Results – The results show that financial performance significantly influences public perception. Companies with higher liquidity and profitability tend to have higher firm value and stronger public trust. Originality/Value – This study emphasizes that maintaining stable financial performance is important for building positive public perception and corporate reputation. Companies should manage financial resources effectively and communicate financial performance transparently to strengthen stakeholder confidence and increase firm value.